Electrochemical deintercalation method for extracting lithium from salt lake and preparation method and application thereof
Patent Information
- Application Number
- CN202380009633.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-03-29
AI Technical Summary
In existing technologies, it is difficult to control the amount of hydrophilic inorganic nano-oxides and binders. Adding too little will result in a lack of significant improvement in the hydrophilicity of the electrode and the mass transfer of the solution, while adding too much will lead to an excessively low proportion of active material in the electrode and a decrease in the lithium extraction per unit area.
By locally modifying the pores of the ion sieve to be superoleophobic and superhydrophilic, an epoxy-modified silica powder is used to form a hydrophilic and oleophobic film in the pores of the ion sieve, thereby improving the hydrophilicity of the mass transfer channels. The amount of modifier added is controlled by adjusting the parameters of the ball mill mixer and the airflow separation device.
This improves the mass transfer efficiency of the solution in the electrode channels, avoids the decrease in the proportion of active material in the electrode and the lithium extraction rate per unit area due to excessive addition of hydrophilic substances, and achieves efficient lithium-ion adsorption capacity and rapid lithium extraction process.
Smart Images

Figure BDA0004326020800000081 
Figure BDA0004326020800000091
Abstract
Description
Technical Field
[0001] This application pertains to the field of lithium extraction from salt lakes, for example, an electrochemical deintercalation / intercalation method for lithium extraction from salt lakes, its preparation method, and its application. Background Technology
[0002] In recent years, supported by national policies, the new energy vehicle industry has developed rapidly, leading to a surge in demand for lithium. Consequently, lithium extraction technology has received increasing attention. my country is one of the world's largest lithium consumers, and lithium resources are also a crucial strategic resource for my country's industrial development. my country's lithium resources are mainly distributed in salt lake brines, making the development of suitable lithium extraction technologies of significant economic and strategic importance. Currently, developed methods for lithium extraction from salt lakes include adsorption, solution extraction, electrodialysis, and electrochemical deintercalation / intercalation.
[0003] Electrochemical deintercalation / intercalation involves using a LiFePO4 / FePO4 electrode as the anode / cathode, and driving lithium ions to intercalate into the FePO4 electrode material via an external circuit to achieve selective lithium extraction. The mass transfer efficiency of lithium ions within the electrode is a key factor affecting the lithium extraction rate in this method. Generally, hydrophilic inorganic nano-oxides and binders are introduced to modify the electrode, improving its hydrophilicity to the solution and reducing the concentration gradient increase during lithium extraction. However, controlling the amount of hydrophilic inorganic nano-oxides and binders is challenging. Insufficient addition will not significantly improve the electrode's hydrophilicity and mass transfer efficiency, while excessive addition will result in a low proportion of active material, leading to a decrease in lithium extraction yield per unit area.
[0004] CN113293290A discloses an electrode material for lithium extraction from salt lakes, its preparation method, and its application. This method improves the selectivity and hydrophilicity of the electrode active material by coating its surface with a graphene oxide / manganese-based ion sieve composite. Using this modified electrode active material as a raw material, inorganic nano-oxides are introduced to modify the binder during electrode preparation. A pore-forming agent is added to prepare a porous electrode, further improving the electrode's affinity for the solution. The presence of the porous structure enhances mass transfer within the electrode, reduces concentration gradient widening during lithium extraction, and improves the electrode's electrochemical performance.
[0005] CN113265538A discloses a method for preparing a highly conductive porous electrode for lithium extraction from salt lakes. The method includes modifying the binder used in the electrode preparation process by blending inorganic nanoparticles and polar hydrophilic organic polymers to improve the binder's hydrophilicity. During the electrode slurry preparation process, an inorganic salt pore-forming agent is added to create pores of varying sizes during drying, improving mass transfer within the electrode plate. Finally, the prepared electrode material undergoes surface chemical modification in a conductive polymer monomer solution.
[0006] The amount of hydrophilic inorganic nano-oxides and binders used in the above scheme is difficult to control. If too little is added, the improvement in the hydrophilicity of the electrode and the mass transfer of the solution will not be significant. If too much is added, the proportion of active material in the electrode will be too low, resulting in a decrease in the lithium extraction per unit area. Summary of the Invention
[0007] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of the claims.
[0008] This application provides an electrochemical deintercalation method for lithium extraction from salt lakes, its preparation method, and its application. This application improves the hydrophilicity of the mass transfer channels and enhances the mass transfer of the solution by locally modifying the pores of the ion sieve to be superoleophobic and superhydrophilic. In addition, it successfully avoids the decrease in the proportion of active material and the decrease in adsorption capacity of the electrode caused by the addition of too much hydrophilic material.
[0009] To achieve the purpose of this application, the following technical solution is adopted:
[0010] In a first aspect, embodiments of this application provide a method for preparing an electrochemical lithium extraction electrode from a salt lake, the method comprising the following steps:
[0011] (1) A mixed solution is obtained by mixing silicon source, silane coupling agent and solvent. An acid solution is added to the mixed solution to obtain a sol. After ultrasonication and aging, an epoxy-modified silica sol is obtained. After freeze-drying, an epoxy-modified silica powder is obtained.
[0012] (2) The ion sieve, epoxy-modified silica powder and binder are mixed, ground and separated to obtain a locally modified ion sieve;
[0013] (3) The locally modified ion sieve, binder and conductive agent are mixed with solvent to obtain electrode slurry, and the electrode slurry is coated on the surface of titanium mesh to obtain the electrochemical deintercalation method lithium extraction electrode from salt lake.
[0014] This application embodiment improves the hydrophilicity of the pores by locally modifying the pores of the ion sieve to be superoleophobic and superhydrophilic, thereby enhancing the mass transfer of the solution in the pores. This preparation method avoids the decrease in the proportion of electrode active material and the lithium extraction per unit area caused by adding too much hydrophilic material.
[0015] In one embodiment, the silicon source in step (1) comprises tetraethyl orthosilicate.
[0016] In one embodiment, the silane coupling agent comprises KH-560.
[0017] In one embodiment, the solvent comprises anhydrous ethanol.
[0018] In one embodiment, the mass ratio of the silicon source, silane coupling agent, and solvent is (1.5–2.5):1:(4–6), for example: 1.5:1:4, 1.8:1:5, 2:1:5, 2.2:1:5.2, or 2.5:1:6, etc.
[0019] In one embodiment, the acid solution in step (1) comprises nitric acid.
[0020] In one embodiment, the mass ratio of the mixed solution to the acid solution is (3.2 to 3.5):1, for example: 3.2:1, 3.3:1, 3.4:1 or 3.5:1, etc.
[0021] In one embodiment, the duration of the ultrasound is 1.5 to 3 hours, for example: 1.5 hours, 1.8 hours, 2 hours, 2.5 hours, or 3 hours.
[0022] In one embodiment, the freeze-drying process includes first freezing at -4°C for 12 hours, followed by freeze-drying at -40°C for 24 hours.
[0023] In one embodiment, the adhesive in step (2) comprises an epoxy resin.
[0024] In one embodiment, the ion sieve includes any one or a combination of two of the following: an iron phosphate ion sieve or a lithium titanate ion sieve.
[0025] In one embodiment, the mass ratio of the epoxy-modified silica powder to the ion sieve is (0.2-1):100, for example: 0.2:100, 0.4:100, 0.6:100, 0.8:100 or 1:100, etc.
[0026] The epoxy-modified silica described in this application exhibits excellent hydrophilic and oleophobic properties. When an epoxy-modified silica hydrophilic and oleophobic film is formed within the pores of the ion sieve, the mass transfer effect of the solution within it is improved. This preparation method successfully avoids the decrease in the proportion of electrode active material and the lithium extraction yield per unit area caused by the addition of excessive hydrophilic substances.
[0027] In one embodiment, the mass ratio of the adhesive to the epoxy-modified silica powder is (0.02-0.1):100, for example: 0.02:100, 0.04:100, 0.06:100, 0.08:100 or 0.1:100, etc.
[0028] With the help of the binder, epoxy-modified silica forms a hydrophilic and oleophobic film in the pores of the ion sieve at high temperature. This local modification avoids the decrease in the proportion of electrode active material and the lithium extraction per unit area caused by the addition of too much hydrophilic material, and improves the mass transfer of the solution.
[0029] In one embodiment, the grinding speed in step (2) is 100 to 200 rpm, for example: 100 rpm, 120 rpm, 150 rpm, 180 rpm or 200 rpm, etc.
[0030] In this embodiment, under the high-speed operation of the ball mill mixer, epoxy-modified silica and epoxy resin enter the pores of the ion sieve; furthermore, by controlling the overall rotation speed of the high-speed ball mill mixer, the amount of epoxy-modified silica and epoxy resin entering the pores of the cathode material can be adjusted.
[0031] In one embodiment, the separation includes airflow separation.
[0032] In one embodiment, the airflow velocity for airflow separation is 10 to 15 m / s, for example: 10 m / s, 11 m / s, 12 m / s, 13 m / s, 14 m / s or 15 m / s, etc.
[0033] In this embodiment, the uniformly mixed particles are fed into an airflow separation device, and the separation of large and small particles is achieved by controlling the wind speed and utilizing the different centrifugal forces experienced by the large and small particles.
[0034] In one embodiment, the adhesive in step (3) comprises polyvinylidene fluoride.
[0035] In one embodiment, the conductive agent comprises acetylene black.
[0036] In one embodiment, the solvent comprises N-methylpyrrolidone.
[0037] In one embodiment, the mass ratio of the locally modified ion sieve, binder, and conductive agent is (6-8):1:(1.5-2.5), for example: 6:1:1.5, 6.5:1:1.8, 7:1:2, 7.5:1:2.2, or 8:1:2.5, etc.
[0038] In one embodiment, the area coated in step (3) is 1500–1800 cm². 2 For example: 1500cm 2 1550cm 2 1600cm 2 1700cm 2 1750cm 2 Or 1800cm 2 wait.
[0039] In one embodiment, the coating density is 70–90 mg / cm³. 2 For example: 70mg / cm 2 75mg / cm 2 80mg / cm2 85mg / cm 2 Or 90mg / cm 2 wait.
[0040] Secondly, embodiments of this application provide an electrochemical deintercalation lithium extraction electrode from a salt lake, which is prepared by the method described in the first aspect.
[0041] Compared with related technologies, this application has the following advantages:
[0042] (1) This application aims to improve the hydrophilicity of the mass transfer channels and enhance the mass transfer of the solution by locally modifying the pores of the ion sieve to be superoleophobic and superhydrophilic. In addition, it successfully avoids the decrease in the proportion of electrode active material and the decrease in adsorption capacity caused by adding too much hydrophilic material.
[0043] (2) Under the high-speed operation of the ball mill mixer, epoxy-modified silica and epoxy resin will enter the pores of the large-particle ion sieve. In addition, by controlling the rotation speed of the ball mill mixer, the amount of epoxy-modified silica and epoxy resin entering the pores of the cathode material can be controlled. When the rotation speed is low, most of the epoxy-modified silica and epoxy resin accumulate on the particle surface and are difficult to enter the cracks and defects on the particle surface. Subsequently, the epoxy-modified silica and epoxy resin remaining on the particle surface will be separated out by the airflow separation device.
[0044] (3) The saturated adsorption capacity of the electrochemical deintercalation method for lithium extraction from salt lakes prepared by the method described in this application can reach more than 32.1 mg / g, and the time required for saturated adsorption can be less than 14.9 h.
[0045] After reading and understanding the detailed description, other aspects can be understood. Detailed Implementation
[0046] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.
[0047] Example 1
[0048] This embodiment provides an electrochemical deintercalation / deintercalation lithium extraction electrode from salt lakes. The preparation method of the electrochemical deintercalation / deintercalation lithium extraction electrode from salt lakes is as follows:
[0049] (1) Tetraethyl orthosilicate, silane coupling agent KH-560 and anhydrous ethanol were mixed and stirred for 10 min at a mass ratio of 2:1:5 to obtain mixture A; 0.21% (volume fraction) dilute nitric acid was added dropwise to mixture A and stirred for 2 h to hydrolyze to obtain sol (the mass ratio of mixture A and nitric acid was 3.4:1); after ultrasonic treatment for 2 h, it was aged at room temperature for 3-4 weeks to obtain epoxy modified silica sol; finally, it was placed in a -4℃ refrigerator for 12 h, and then placed in a -40℃ freeze dryer for 24 h to obtain epoxy modified silica powder;
[0050] (2) Take a ferric phosphate ion sieve, epoxy-modified silica, and epoxy resin and ball mill them thoroughly in a high-speed ball mill for 1 hour. After ball milling, send the material into an airflow separation device to separate the ferric phosphate ion sieve and the epoxy-modified silica that is not embedded in the pores of the positive electrode material. Finally, dry the ferric phosphate ion sieve in a 100°C oven to obtain a partially modified ferric phosphate ion sieve. The mass ratio of the epoxy-modified silica to the positive electrode material is 0.5%; the ball mill speed is 150 rpm; the airflow velocity in the airflow separation device is 12 m / s; and the mass ratio of the epoxy resin binder to the epoxy-modified silica is 0.05%.
[0051] (3) Weigh locally modified iron phosphate ion sieve, PVDF, and acetylene black according to a mass ratio of 7:1:2, mix thoroughly, add N-methylpyrrolidone (NMP), and stir under vacuum for 6 hours to obtain an electrode slurry. Coat the slurry onto a titanium mesh using a scraping method, and finally dry it in a vacuum drying oven at 80℃ for 12 hours. The slurry coating area is 1680 cm². 2 The coating density is 80 mg / cm³. 2 The electrochemical deintercalation method lithium extraction electrode from salt lakes was obtained.
[0052] Example 2
[0053] This embodiment provides an electrochemical deintercalation / deintercalation lithium extraction electrode from salt lakes. The preparation method of the electrochemical deintercalation / deintercalation lithium extraction electrode from salt lakes is as follows:
[0054] (1) Tetraethyl orthosilicate, silane coupling agent KH-560 and anhydrous ethanol were mixed and stirred for 10 min at a mass ratio of 2.2:1:5.2 to obtain mixture A; 0.21% (volume fraction) dilute nitric acid was added dropwise to mixture A and stirred and hydrolyzed for 2 h to obtain sol (where the mass ratio of mixture A and nitric acid was 3.5:1); after ultrasonic treatment for 2 h, it was aged at room temperature for 3-4 weeks to obtain epoxy modified silica sol; finally, it was placed in a -4℃ refrigerator for 12 h, and then placed in a -40℃ freeze dryer for 24 h to obtain epoxy modified silica powder;
[0055] (2) Take a ferric phosphate sieve, epoxy-modified silica, and epoxy resin and ball mill them thoroughly in a high-speed ball mill for 1 hour. Then, send the material into an airflow separator to separate the ferric phosphate sieve and the epoxy-modified silica that is not embedded in the pores of the cathode material. Finally, dry the ferric phosphate sieve in a 100°C oven to obtain a partially modified ferric phosphate sieve. The mass ratio of the epoxy-modified silica to the cathode material is 0.6%; the ball mill speed is 100 rpm; the airflow velocity in the airflow separator is 14 m / s; and the mass ratio of the epoxy resin binder to the epoxy-modified silica is 0.06%.
[0056] (3) Weigh locally modified iron phosphate ion sieve, PVDF, and acetylene black according to a mass ratio of 7:1:2, mix thoroughly, add N-methylpyrrolidone (NMP), and stir under vacuum for 6 hours to obtain an electrode slurry. Coat the slurry onto a titanium mesh using a scraping method, and finally dry it in a vacuum drying oven at 80℃ for 12 hours. The slurry coating area is 1680 cm². 2 The coating density is 80 mg / cm³. 2 The electrochemical deintercalation method lithium extraction electrode from salt lakes was obtained.
[0057] Example 3
[0058] The only difference between this embodiment and Embodiment 1 is that the ball mill mixer speed is 50 rpm and the airflow velocity of the airflow separator is 15 m / s. All other conditions and parameters are exactly the same as in Embodiment 1.
[0059] Example 4
[0060] The only difference between this embodiment and Embodiment 1 is that the ball mill mixer speed is 200 rpm and the airflow velocity of the airflow separator is 10 m / s. All other conditions and parameters are exactly the same as in Embodiment 1.
[0061] Comparative Example 1
[0062] The only difference between this comparative example and Example 1 is that no modification treatment is performed on the ion sieve; all other conditions and parameters are exactly the same as in Example 1.
[0063] Ferric phosphate ion sieve, PVDF, and acetylene black were weighed out in a mass ratio of 7:1:2, thoroughly mixed, and then N-methylpyrrolidone (NMP) was added and stirred under vacuum for 6 hours to obtain an electrode slurry. The slurry was coated onto a titanium mesh using a scraping method and then dried in a vacuum drying oven at 80°C for 12 hours. The coating area of the slurry was 1680 cm². 2 The coating density is 80 mg / cm³. 2 The electrochemical deintercalation method lithium extraction electrode from salt lakes was obtained.
[0064] Comparative Example 2
[0065] The difference between Comparative Example 2 and Comparative Example 1 is that hydrophilic nano-silica, accounting for 30% of the total mass, is added in step (2).
[0066] Performance testing:
[0067] The iron phosphate electrodes prepared in Examples 1-6 and Comparative Examples 1-2 were placed as cathodes in a cathode chamber containing 15 g / L LiCl solution, and the lithium iron phosphate electrode was placed as anode in an anode chamber containing 30 g / L NaCl solution. Lithium insertion / deintercalation was performed using a constant current followed by a constant voltage process until the current was less than 2 A / m. 2 The test results are shown in Table 1:
[0068] Table 1
[0069]
[0070]
[0071] As can be seen from Table 1, as obtained from Examples 1-2, the saturated adsorption capacity of the electrochemical deintercalation method for lithium extraction from salt lakes prepared by the method described in this application can reach more than 32.1 mg / g, and the time required for saturated adsorption can be less than 14.9 h.
[0072] A comparison of Examples 1 and 3-4 shows that as the ball mill mixer speed increases, more and more epoxy-modified silica and epoxy resin binder are embedded in the pores of the ion sieve, resulting in better hydrophilic and superoleophobic effects within the pores. This allows the solution to flow freely and quickly in the electrode channels without obstruction (low solution diffusion resistance), improving the mass transfer effect of the solution and increasing the adsorption capacity of the electrode for lithium ions.
[0073] As can be seen from the comparison between Example 1 and Comparative Example 1, this application improves the hydrophilicity of the pores by locally modifying the pores of the ion sieve to be superoleophobic and superhydrophilic, thereby improving the mass transfer of the solution in the pores and significantly shortening the time required for saturation adsorption.
[0074] As can be seen from the comparison between Example 1 and Comparative Example 2, the epoxy-modified silica described in this application has good hydrophilic and oleophobic properties. When an epoxy-modified silica hydrophilic and oleophobic film is formed in the pores of the ion sieve, the mass transfer effect of the solution inside it is improved. This preparation method successfully avoids the decrease in the proportion of electrode active material and the lithium extraction per unit area caused by the addition of too much hydrophilic material.
Claims
1. A method for preparing an electrode for lithium extraction from salt lakes via an electrochemical intercalation / deintercalation method, the method comprising the following steps: (1) A mixed solution is obtained by mixing silicon source, silane coupling agent and solvent. An acid solution is added to the mixed solution to obtain a sol. After sonication and aging, epoxy modified silica sol is obtained. Epoxy modified silica powder is obtained by freeze drying. The silicon source is tetraethyl orthosilicate; the silane coupling agent is KH-560. (2) The ion sieve, epoxy-modified silica powder and binder are mixed, ground and separated to obtain the locally modified ion sieve; The mass ratio of the epoxy-modified silica powder to the ion sieve is (0.2~1):100; The mass ratio of the adhesive to the epoxy-modified silica powder is (0.02~0.1):100; The ion sieve is any one or both of iron phosphate ion sieve and lithium titanate ion sieve. The grinding speed is 100~200 rpm; (3) The locally modified ion sieve, binder and conductive agent are mixed with solvent to obtain electrode slurry, and the electrode slurry is coated on the surface of titanium mesh to obtain the electrochemical deintercalation method lithium extraction electrode from salt lake.
2. The preparation method according to claim 1, wherein, The solvent includes anhydrous ethanol.
3. The preparation method according to claim 1, wherein, The mass ratio of the silicon source, silane coupling agent, and solvent is (1.5~2.5):1:(4~6).
4. The preparation method according to claim 1, wherein, The acid solution in step (1) includes nitric acid.
5. The preparation method according to claim 1, wherein, The mass ratio of the mixed solution to the acid solution is (3.2~3.5):
1.
6. The preparation method according to claim 1, wherein, The ultrasound time in step (1) is 1.5~3h.
7. The preparation method according to claim 1, wherein, The adhesive in step (2) includes epoxy resin.
8. The preparation method according to claim 1, wherein, The separation includes airflow separation.
9. The preparation method according to claim 8, wherein, The airflow velocity for airflow separation is 10~15m / s.
10. The preparation method according to claim 1, wherein, The adhesive in step (3) includes polyvinylidene fluoride.
11. The preparation method according to claim 1, wherein, The conductive agent includes acetylene black.
12. The preparation method according to claim 1, wherein, The solvent includes N-methylpyrrolidone.
13. The preparation method according to claim 1, wherein, The mass ratio of the locally modified ion sieve, binder, and conductive agent is (6~8):1:(1.5~2.5).
14. The preparation method according to claim 1, wherein, The area coated in step (3) is 1500~1800cm². 2 .
15. The preparation method according to claim 1, wherein, The coating density is 70~90 mg / cm³. 2 .
16. An electrochemical deintercalation lithium extraction electrode from a salt lake, wherein the electrochemical deintercalation lithium extraction electrode is prepared by the method described in any one of claims 1-15.
Citation Information
Patent Citations
Preparation method of high-conductivity porous electrode for extracting lithium from salt lake
CN113265538A
Electrode material for salt lake lithium extraction and preparation method and application of electrode material
CN113293290A
Organic-inorganic hybridization ultraviolet cured paint for protecting metallic surface
CN101307194A
Preparation method of hydrophilic lithium extraction electrode
CN113293289A
